The Cross-Partisan Voices of Podcasts and Their Social Media Ties - DeMets, Sydney; Saveski, Martin (Proceedings of the International AAAI Conference on Web and Social Media, 2026)
Heightened polarization in the United States has raised public and scholarly concern about podcasts and their role in political division. Podcasts that repeatedly host cross-partisan discussions, however, remain understudied. In this work, we examine whether individuals who engage with politically heterogeneous voices on podcasts also display bridging behavior on social media and in their cross-cutting conversations. Specifically, we investigate whether bridging actors follow a more politically diverse set of accounts on social media and whether they discuss topics that differ from those of their non-bridging counterparts. To do so, we collect data on roughly 5,000 individuals who appeared on popular political podcasts over a 13-month period, including their podcast appearances and discussion content. We also identify their X accounts and extract the follower relationships among them. We find that podcasters and their guests interact with a smaller but more politically diverse set of individuals on podcasts than on X, except for liberal podcasts, which maintain similar cross-cutting ties across both media. To study cross-ideological conversation, we transcribed and diarized over 10,000 podcast episodes. We find that bridging guests tend to discuss a narrower set of topics during cross-cutting podcast interviews compared to non-bridging guests. These findings indicate that bridging actors in the podcasting space exhibit distinguishable conversational and attentional behaviors, laying the groundwork for further research examining these actors and their conversations across various media.